Perceived effects and coping mechanisms of rape victims among University of Ibadan undergraduates (2018)
The Prevalence of rape and its associated consequences in the Nigerian society has attracted global and scholarly attention. Several studies on rape have focused on the act of rape itself, the consequences, characteristics of Perpetrators and legal implication of rape. Few however, have focused on the perceived effects of rape and the Coping mechanisms adopted by victims especially in Oyo state. This necessitated the focus of this study. Differential Association theory and Social bond/control theory formed the theoretical frame work for the study. Quantitative data were elicited from 499 respondents selected using LeslieKish’s formula, while qualitative data Were elicited from 4 case studies, 5in-depth interviews (IDI) and one key informant interview (KII).Quantitative Data were analyzed using descriptive statistics such as percentages, chart s and cross-tabulation, while qualitative Data were content analyzed A huge proportion (93%) reported that rape adversely affects the victims. The most perceived effects of rape were psychological (92.4%), with low self esteem, mood swings, depression, and perpetual Anger being reported by 87.2%, 81.0% and 77.0% respectively. Health effect such as HIV (87.6%), Sexual Transmitted Diseases (STDs) (88.0%), pregnancy (82.6%), abortion (62.3%), damages of reproductive organs (62.9%), and death (66.7%) were reported by respondents respectively. Seeking psychological and medical help to Live a normal life and voicing out for the police to look into was suggested by 89.0% and about 60.0% as the coping Methods victims adopted. There is need for collective enlightenment of women in all sectors on the menace and effects of rape.